The comparative assessment of the of the effectiveness of immediate and delayed dental implantation - Gagik Hakobyan; Lazar Esayan; Davit Hakobyan; Gagik Khachatryan; Gegham Tunyan (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2020)
Objective: The purpose of this study was to evaluate the outcome of immediate and delayed implant placment protocols. Materials and methods: The 52 patients with missing thoot (from 2014 to 2019) were selected for the study, total 64 implants were placed. All patients presented functional and esthetic complaints and underwent a thorough clinical examination according to a generally accepted scheme. Computed tomography were obtained to determine the osseos structure.  To conduct a comparative analysis of the treatments results, two groups were formed: -Basic group of 28 patients -were placed 36 immediate implants. -Control group of 24 patients-3-5 months after extraction of tooth were placed 28 delayed implants. Postoperative outcomes; infection, radio-density, resorption and failure of implants were checked clinically and radiographically using serial orthopantomograms or CT scan. The implants stability were evaluated with measures of resonance frequency analysis (RFA) during the follow-up periods using Osstell Mentor at time of implant placement, after 3-6 months. The functional load on dental implants was performed with ISQ values above 65. Dental prosthetic rehabilitation was performed after 3-6 months of submerged healing in 35 patients. Early dental prosthetic loaded in 17 patients (9 patients in basic group and 8 control group). Results: No serious intraoperative or immediate postoperative complications were noted. After a 24-month follow-up period, the basic group resulted in a mean bone loss of 1.04 and the control group of 1.02mm, there were no statistically significant differences. Clinical comparing delayed and immediate implant placement there were no statistically significant differences effect on soft tissue recession outcomes. Clinical outcome of implants immediately placed into extraction sockets of teeth affected by chronic lesions was examined. 11 Patients with periapical infection and 17 patients without it for immediate placement were chosen. No significant differences were found with periapical infection and without in the basic group patients, no signs of infection around the implants were detected at any control visit. The survival rate of early-loaded implants placed in extraction sockets demonstrated no implants failures. There are no significant differences in implant stability between immediate and delayed implants. Immediately placed implants were included with an initial primary stability over 65 ISQ and 71.1 ISQ delayed implants. The differences in these results were not statistically significant. Success rate of immediately placed implants 5 years after was 97,8% and delayed implants 98,1%. The survival rate of early-loaded implants placed in extraction sockets 96,2%. Conclusion: There are no significant differences in immediate and delayed implants. After dental implant prosthetic rehabilitation, the masticatory function, esthetics of the facial profile and occlusion was improved.